Prehistoric Modernization - Chen, Shengqian. author. aut Link
XL, 531 p. 45 illus., 20 illus. in color.
Keywords: This book explores the origins of agriculture in China, and the transformation from hunter-gatherer to agriculture producer. Therefore, it reveals the ancient genes of China as an agricultural country and digs into questions like what turning events occurred during the transformative period from hunting-gathering to agricultural production and why the development of agriculture is rapid in some regions while largely delayed in others. This book also introduces various definitions and theoretical methods on the study of agriculture’s origin. It represents the transforming era by simulating prehistoric hunter-gatherer’s survival strategies with data collected from modern weather station. The author also tries to answer questions on the origins of agriculture production in China with comprehensive archeology evidences. CHEN, Shengqian is a professor and tutor for graduate students of the Department of Archaeology and Museology in School of History, Renmin University of China. In 2004, he earned his Ph.D. at the Southern Methodist University (SMU) in the United States. His main research fields are archeological theory, history of archaeological thoughts, agricultural origins, stone tool analysis, prehistoric art and archaeological education. Chen engaged in writings on archaeological theory and method, archaeological education and prehistory. He is also the author of Learning Archaeology, Thinking about Archaeology, In Pursuit of Human and other several books.